Technosols constructed from urban waste enhance carbon stabilization through improved soil aggregation - Thalita Fernanda Abbruzzini; Blanca Lucia Prado Pano; Lucy Mora Palomino; Alan Ulises Loredo-Jasso; María del Pilar Ortega Larrocea; Ceres Perez Vargas; Victor Manuel Peña Ramirez (EQA)
This study investigates the distribution and stabilization of carbon (C) in technosols constructed from urban waste materials and organic inputs, aiming to enhance C storage and restore urban ecosystems. Technosols composed of concrete (Cw) and excavation (Ew) waste, wood chips (W), compost (C), and biochar (B) (CwO, EwO, and WCB) were analyzed over two years within an urban milpa, a traditional Mesoamerican agricultural system. We assessed C and nitrogen (N) contents, exchangeable cations, aggregate size distribution, and molecular composition. Among the technosols, the wood chip, compost, and biochar mixture (WCB) exhibited the highest organic C (OC), inorganic C (IC), and total N (TN) contents, followed by CwO and EwO. While C levels remained stable in all technosols, TN decreased in CwO, increasing its C/N ratio to 27, indicating potential N immobilization. Calcium concentrations increased across all technosols (CwO = WCB > EwO), while Na levels decreased, improving aggregate stability. Macroaggregates accounted for 85% of OC and TN in all technosols, with microaggregates and silt + clay fractions containing 5% and 10%, respectively. CwO and EwO exhibited particulate organic matter occlusion within macroaggregates, while EwO had more microaggregates and silt + clay particles. FTIR analysis confirmed the presence of carbonates in all aggregate sizes and showed that the molecular composition of stabilized C varied, with more recalcitrant compounds found in microaggregates. These results highlight the importance of managing cation balances, particularly increasing Ca2+ and reducing Na+, to improve soil structure and enhance C stabilization.